Supervisory Practices and the Profile of the Ideal Supervisor from the PhD Student’s Perspective - Ribau, Isabel (Advances in Social Sciences Research Journal, 2024)
Implementing qualification frameworks in response to the Bologna process during the latter part of the 20th century prompted considerable change regarding Higher Education. Such alterations brought up apprehensions concerning the acquisition of competencies following each cycle of studies, as well as the means employed to oversee and assess teaching and learning procedures. The NOVA University of Lisbon (UNL) has recently researched Doctoral Education, focusing on supervisory practices. Since 2018, surveys regarding doctoral supervision have been conducted across multiple schools at UNL. This research report presents an overview of the national numbers regarding doctoral education enrollment, and the results of a study conducted at four schools within the UNL: the National School of Public Health (ENSP), Technological Institute of Chemistry and Biochemistry (ITQB), NOVA Medical School | FCM NOVA, and NOVA School of Science and Technology | FCT NOVA. The study presents data regarding part-time PhD students’ and full-time PhD students’ views of the supervisor rule and focuses on examining the characteristics of an ideal supervisor and the supervision practices experienced by doctoral students throughout their PhD programs. The findings suggested that supervision practices were slightly different considering the type of attendance, the enrolment year (during all doctoral research projects), and the schools’ culture and field (Health or Science and Technology). Furthermore, the supervisor’s role (mentor or coach) was similar within the school field, but the “ideal” supervisor varied depending on the school attendance type.